Conhecendo o infinito e seus paradoxos - Iseppi, Pedro Henrique (2023)
Infinity has intrigued human beings since man learned to think. If we observe the principle of counting and ordering, the sequence (1, 2, 3, 4, ... ) already brings with it a dilemma, as it is a sequence that never ends and we cannot imagine a number tha is greater than all others. From this perspective, the present work studies some ideas related to this concept, since ancient Greece, with the emergence of paradoxes until the 19th centyry, in which the mathematician Georg Cantor (1845-1918) demostrated the existence of different infinities. Therefore, the objetive of this work is to understand what infinity is, more specifically infinity, the mathematical conception, and explain it clearly and succinctly to facilitate the undsertanding of this concept, regardless of the audience that uses it.